2012
DOI: 10.1016/j.biomaterials.2012.07.042
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stromal cell-derived factor-1α/heparin coating of biodegradable vascular grafts on the recruitment of both endothelial and smooth muscle progenitor cells for accelerated regeneration

Abstract: Small-diameter synthetic vascular grafts have high failure rate and tissue-engineered blood vessels are limited by the scalability. Here we engineered bioactive materials for in situ vascular tissue engineering, which recruits two types of endogenous progenitor cells for the regeneration of blood vessels. Heparin was conjugated to microfibrous vascular grafts to suppress thrombogenic responses, and stromal cell-derived factor-1α (SDF-1α) was immobilized onto heparin to recruit endogenous progenitor cells. Hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(139 citation statements)
references
References 42 publications
(35 reference statements)
4
132
0
Order By: Relevance
“…[18][19][20][21][22] Providing further evidence for this phemonmenon, implanted scaffolds with low porosity 28,30,32 and even TEBVs with already intact SMC layers 24 have been shown to be repopulated with host vessel wall cells. In addition, vascular engineering methods have begun to take advantage of host recellularization by creating acellular approaches, utilizing bound growth factors or drug delivery methods, 19,23,96 or designing porous scaffolds to facilitate this cellular infiltration. 31,46,97,98 In all of these cases, establishing a mature TEBV populated by SMCs requires recruitment of host cells.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22] Providing further evidence for this phemonmenon, implanted scaffolds with low porosity 28,30,32 and even TEBVs with already intact SMC layers 24 have been shown to be repopulated with host vessel wall cells. In addition, vascular engineering methods have begun to take advantage of host recellularization by creating acellular approaches, utilizing bound growth factors or drug delivery methods, 19,23,96 or designing porous scaffolds to facilitate this cellular infiltration. 31,46,97,98 In all of these cases, establishing a mature TEBV populated by SMCs requires recruitment of host cells.…”
Section: Figmentioning
confidence: 99%
“…In vascular tissue engineering, this paracrine signaling appears to be an important mechanism [18][19][20][21][22] by which tissueengineered blood vessels (TEBVs) remodel. Recent studies have shown they possess a dynamic environment that is repopulated with host cells, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] such as by the inward migration of vascular smooth muscle cells (SMCs).…”
Section: Introductionmentioning
confidence: 99%
“…Bridging the gap between heparin-treated prostheses and tissue engineering are developments such as SDF1a/heparin-coated vascular grafts for the recruitment of progenitor cells (Yu et al, 2012).…”
Section: B Heparin-treated Medical Devicesmentioning
confidence: 99%
“…Recruitment of endothelial progenitor cells was enhanced through the cumulative release of SDF-1. In addition, Yu et al (2012) showed increased migration and differentiation of smooth muscle progenitor cells. The growth factor BMP-2 can bind to several polysaccharides (Tables 3 and 4).…”
Section: Multifunctional Coatings To Simultaneously Modulate Diverse mentioning
confidence: 98%
“…The strong interaction of heparin and SDF-1 was also applied for the coating of cardiovascular devices. Yu et al (2012) and Lee et al (2013b) described the increased stability of the chemokine SDF-1 when present in a coacervate with heparin. Recruitment of endothelial progenitor cells was enhanced through the cumulative release of SDF-1.…”
Section: Multifunctional Coatings To Simultaneously Modulate Diverse mentioning
confidence: 99%